Web 2.0 revisited: user-generated content as a social innovation. (14th October 2011) - Pelka, Bastian; Kaletka, Christoph
This paper raises the question whether Web 2.0 can be seen as a technological or a social innovation and which interdependencies exist between these two innovative aspects of the phenomenon. For that purpose, the definition of Web 2.0 as a tag cloud (for example given in Wikipedia) or as a difference in comparison to a ?Web 1.0? is revisited, challenged and discarded. In following steps, the paper argues that the core innovation of Web 2.0 is the communication of ?user-generated content? as a new social routine. The main enabling factors for Web 2.0 utilisation as a social routine are identified as easy-to-use software and broadly spread internet access. So while technology is seen as a ?catalyst? of the phenomenon, the innovation itself (user-generated content) is considered a social one.